Odpowiedzi

Najlepsza Odpowiedź!
2009-12-02T18:03:40+01:00
4-{(5x)^2-2^2]-[3^2+(5x)^2-2*3*5x+50^2=4-(25x^2-4)-(9+25^2-30x)+50^2=4+25x^2+4-9-25^2-30x+50^2=-1-30x=-1-30*(-3)=-1+90=89

-2x(x-y)+(y-3)^2+(y-3x)(y+3x)+2xy=-2x^2+2xy+(y^2+3^2-2*3*y)+[y^2-(3x)^2]+2xy=-2x^@+2xy+y^2+9-6y+y^2-9x^2+2xy=-11x^2+4xy+2y^2+9-6y=-11*(-1)^2+4*(-1)*2+2*2^2+9-6*2=-11-8+8+9-12=-14

(2x-3)*(2x+3)-(3x-2)^2-4x^2=(2x)^2-3^2-[(3x)^2+2^2-2*3x*2]-4x^2=4x^2-9-(9x^2+4-12x)-4x^2=4x^2-9-9x^2-4+12x-4x^2=-9x^2-13+12x=-9*(-1)^2-13+12*(-1)--9-13-12=-34